Zoolexis in Semantic Aspect (by Example of Nouns Derived from Zoonyms) - Y. Geng; G. N. Plotnikova (Научный диалог)
The article is devoted to semantic analysis zoonymic vocabulary of the Russian language. The paper presents definitions of terms zoonym and zoolexis . The characteristic of Russian nouns derived from zoonyms is given from the point of view of grammatical semantics. In accordance with the nature of grammatical semantics of nouns derived from zoonyms their semantic classes are distinguished. The focus is on the description of the whole semantic groups of nouns derived from zoonyms with a particular meaning. The relevance of the study is determined by the fact that nouns derived from zoonyms with the meaning of a particular item represent a considerable variety among all nouns derived from zoonyms (383 of 489 recorded in derivational dictionary) and are an important part of zoonymic vocabulary in nominative and communicative aspect. On the basis of definition and contextual analysis of lexical units the authors divided them into groups. It is shown that the semantic grouping of nouns derived from zoonyms with the specific meaning depend on belonging to a lexico-grammatical category of animate or inanimate nouns, as lexical representatives of each category form different semantic groups that have certain characteristics. The novelty of the research is seen in the fact that for the first time the Russian nouns derived from zoonyms and naming animals fully analysed from the point of view of semantics.